2015
DOI: 10.1016/j.resuscitation.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcomes of rearrest following out-of-hospital cardiac arrest

Abstract: Introduction Rearrest occurs when a patient experiences cardiac arrest after successful resuscitation. The incidence and outcomes of rearrest following out-of-hospital cardiac arrest have been estimated in limited local studies. We sought provide a large-scale estimate of rearrest incidence and its effect on survival. Methods We obtained case data from emergency medical services-treated, out-of-hospital cardiac arrest from the Resuscitation Outcomes Consortium, a multi-site clinical research network with cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 11 publications
3
25
0
1
Order By: Relevance
“…[6][7][8] The study presented in the last issue of Resuscitation uses several methods to detect rearrest, all retrospective and all flawed. 1 The variability observed between regions and systems in this current multi-center study mirrors the variability demonstrated in previous publications, [3][4][5] and illustrates many of the problems that occur in attempts to compare retrospective data collected in different ways. Yet the sheer volume and persistence of significant rearrest events, even with the most conservative estimates underscores the clinical relevance of the rearrest issue and the importance of high quality post-resuscitation care from the moment circulation is restored.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…[6][7][8] The study presented in the last issue of Resuscitation uses several methods to detect rearrest, all retrospective and all flawed. 1 The variability observed between regions and systems in this current multi-center study mirrors the variability demonstrated in previous publications, [3][4][5] and illustrates many of the problems that occur in attempts to compare retrospective data collected in different ways. Yet the sheer volume and persistence of significant rearrest events, even with the most conservative estimates underscores the clinical relevance of the rearrest issue and the importance of high quality post-resuscitation care from the moment circulation is restored.…”
supporting
confidence: 80%
“…In the last issue of Resuscitation, Salcido and colleagues give us some preliminary insight into the largely ignored, yet critical time period from initial return of circulation to stabilization in intensive care unit. 1 There are some earlier retrospective accounts of rearrest including previous work by the authors. While rearrest is reported to be uncommon (6%) in the setting of secondary transports by highly specialized teams, 2 rearrest during primary transport to hospital has been reported to occur in somewhere between 5% and 40% of patients who regain spontaneous circulation out-of-hospital.…”
mentioning
confidence: 99%
“…Accordingly, several studies have investigated the extent to which the chances of resuscitation and survival vary over different conditions [6][7][8][9][10] including the types of symptoms, treatment provided [11][12][13] , patients' attributes 14,15 and situations 5,[16][17][18][19][20] . These previous studies have mostly utilized monthly observations of OHCA cases that had already occurred to investigate outcomes in relation to emergency care procedures.…”
Section: Introductionmentioning
confidence: 99%
“…An estimate of rearrest incidence derived from 2008 – 2011 showed that between 16.5% and 38.4% of all cases with ROSC developed a rearrest prior to hospital arrival. 6 Unlike the present study, the older study did not benefit from specific rearrest data fields in ROC data forms, and a large portion of rearrest ascertainment involved secondary inference. We did not find a significant temporal trend in rearrest incidence, however we did find a significant difference in rearrest incidence between the ROC sites.…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies have shown that rearrest occurs in 5% to 39% of all cases achieving ROSC and is associated with reduced probability of survival to hospital discharge. 26 Considering this, prevention or prediction of rearrest could present a significant opportunity to increase survival after OHCA. However, to date there is little evidence for predicting prehospital rearrest, either by patient characteristics or procedural factors.…”
Section: Introductionmentioning
confidence: 99%